Chinese Herbal Complex 'Bu Shen Jie Du Fang' (BSJDF) Modulated Autophagy in an MPP+-Induced Cell Model of Parkinson's Disease. (13th March 2019) - Liu, Cuifang; Huang, Xiaobo; Qiu, Shengxiang; Chen, Wenqiang; Li, Weihong; Zhang, Haiyan; Wang, Tao; Wang, Xue; Wu, Xiling
Abstract : Autophagy plays an important role in the development of Parkinson disease (PD). Previous studies showed that autophagy could protect cells from α -synuclein toxicity and promote functional coupling of mitochondria. But it is still a question whether modulating autophagy can be used to treat PD. In traditional Chinese medicine, a specific Chinese herbal complex called Bu Shen Jie Du Fang (BSJDF) has a long history of treating motor impairments similar to Parkinson disease, while its mechanism is still unclear. As a pilot study, we aimed to evaluate the efficacy and its mechanism of Bu Shen Jie Du Fang in an MPP + -induced cell model of Parkinson's disease. And the phase contrast microscope (PCM) revealed that the BSJDF group had the greatest surviving cell counts compared with all other treated cell groups except the normal group. And Cell Counting Kit 8 (CCK8) assays showed a similar result. In BSJDF group, 3.7 ×10 7 cells/dish was identified by hemocytometer counts, which was significantly higher than other groups except the normal cells (p<0.05). In the BSJDF group, autophagy can be observed by transmission electron microscopy (TEM). Protein expression of Atg12 and LC3 in the BSJDF group was upregulated compared to the PD model group (p<0.05). Atg12 mRNA expression was also upregulated in the BSJDF group (p<0.05). In conclusion, our study indicated that the therapeutic mechanisms of BSJDF may be mediated by stimulating autophagy, and modulating autophagy can be used to treat PD.